Fresh fields and pastures new : papers presented in honor of Andrew M.T. Moore - Lillios, Katina T., 1960-; Chazan, Michael; Moore, A. M. T. (Andrew Michael Tangye) (Sidestone Press, 2016)
This volume honors the career and contributions of Andrew M.T. Moore. Moore's groundbreaking work at Abu Hureyra, Syria and excavations at neolithic sites in Croatia have made him a pioneer in integrated interdisciplinary research in archaeology, expressing a deeply held conviction that developments in human culture can only be understood when embedded in an ecological approach. In this book, colleagues and former students of Moore, working in the Near East and Croatia, present current research, illustrating the continuing impact of Moore's work on the early farming and herding peoples of the eastern Mediterranean.